Physically tailoring ion fluxes by introducing foamlike structures into polymeric membranes of solid contact ion-selective electrodes - Cheong, Yi Heng (2022)
Transmembrane ion fluxes have earlier been identified as a source of potential instability in solid contact ion-selective electrodes (SC-ISEs). In this work, foamlike structures were intentionally introduced into a potassium-sensitive plasticized poly(vinyl chloride) ion-selective membrane (ISM) near the membrane|solid contact interface by controlling the temperature during membrane deposition. Foamlike structures in the ISM were shown to be effective at physically tailoring the transport of ions in the ion-selective membrane, greatly reducing the flux of interfering ions from the sample to the membrane|solid contact interface. The drifts during a conventional water layer test were hence able to be greatly mitigated, even with SC-ISEs incorporating a relatively hydrophilic poly(3,4-ethylenedioxythiophene) doped with poly(styrenesulfonate) (PEDOT:PSS) solid contact. In solutions with a high background concentration of interfering ions, equilibrated ion-selective electrodes with foamlike membranes were able to reproduce their initial potentials within 0.6 mV uncertainty (n = 3) from 0 to 18 h. This was achieved despite sensor exposure to solutions exceeding the selectivity limit of the ISEs in 3 h intervals, allowing improvement of the potential reproducibility of the sensors. Since the introduction of foamlike structures into ISM is linked to temperature-controlled membrane deposition, it is envisaged that the method is generally applicable to all solid contact ion-selective electrodes that are based on polymeric membranes and require membrane deposition from the cocktail solution.